Antistatic black porous alumina ceramic and preparation method and application thereof

CN123003264APending Publication Date: 2026-10-30SHANGHAI UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510536184.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该方法用物理混合的预合成黑色颜料(Co2O3-Fe2O3-MnO2-NiO焙烧产物)在流延成型中可能易因密度差异导致成分偏析,形成局部色差,并且颜料仅附着于Al2O3颗粒表面,烧结后无法实现体相着色,切割或磨损后可能存在非黑色基体,而原料中的助剂TiO2和La2O3易与着色剂生成高阻相(如La2Ti2O7),导致电阻率波动较大,影响材料的防静电特性

Benefits of technology

[0015]较佳地,步骤(4)中,所述预烧的温度为500~800℃,时间为1~3h;所述烧结为常压烧结;优选地,所述常压烧结的温度为1250~1500℃,时间为2~5h。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003264A_ABST
    Figure CN123003264A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of inorganic nonmetallic materials, and particularly relates to an anti-static black porous alumina ceramic as well as a preparation method and application thereof. The anti-static black porous alumina ceramic comprises a porous alumina ceramic matrix and (Fe x Mn y Co z Ni w )Al2O4 spinel uniformly distributed in the alumina ceramic matrix, wherein x+y+z+w=1, 0.2<=x<=0.8, 0.1<=y<=0.6, 0.05<=z<=0.2, and 0.05<=w<=0.2; the (Fe x Mn y Co z Ni w )Al2O4 spinel is generated by in-situ reaction of alumina and transition metal oxides composed of iron oxide, cobalt oxide, nickel oxide and manganese dioxide; the mass ratio of the iron oxide, the cobalt oxide, the nickel oxide and the manganese dioxide is (4-10):(0.5-2):(1.5-4):(3-8). The application promotes the in-situ generation of stable spinel phase of alumina and the transition metal oxide colorant at high temperature by designing the special proportion and special composition of the colorant, so that the coloring of the black alumina ceramic is more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic non-metallic materials technology, specifically relating to an antistatic black porous alumina ceramic, its preparation method, and its application. Background Technology

[0002] With the continuous development of the microelectronics industry, the demand for high-precision, high-performance vacuum chucks for component clamping is increasing. In semiconductor wafer processing, vacuum chucks must simultaneously meet the following requirements: the material has a porous structure (porosity ≥ 30%) to maintain the chuck's adsorption of the wafer under negative pressure conditions; and the volume resistivity is ≥ 10. 9 ~10 12 Ω·cm to eliminate the effect of static electricity on wafer damage; black surface (L* value < 35) to avoid stray light interfering with photolithography accuracy.

[0003] Traditional porous alumina ceramics are typically white or gray, making it difficult to meet the demand for black materials in specific applications (such as semiconductor devices, ocean desalination, photothermal conversion, and electromagnetic shielding). Existing methods for preparing black porous alumina often involve secondary reduction and surface coating, which result in cumbersome steps, uneven coloring, and difficulties in achieving a balance between porosity and strength.

[0004] Chinese Patent CN 107406328A describes a black alumina ceramic powder obtained by calcining a mixture of Fe2O3, NiO, MnO2, and Co2O3 to obtain a black pigment. Then, according to a formula, Al2O3, the black pigment, SiO2, TiO2, and La2O3 are weighed and mixed in a mixing device to obtain the black alumina ceramic powder. Solvents, dispersants, binders, and plasticizers are added to the black alumina ceramic powder. After grinding, it is cast into a green body under vacuum treatment. The green body is then sintered to prepare the black alumina ceramic body. This method uses a physically mixed pre-synthesized black pigment (Co2O3-Fe2O3-MnO2-NiO calcined product). During tape casting, the pigment may easily segregate due to density differences, resulting in local color differences. Furthermore, the pigment only adheres to the surface of Al2O3 particles, failing to achieve bulk coloring after sintering. After cutting or abrasion, a non-black matrix may remain. Additionally, the additives TiO2 and La2O3 in the raw materials readily react with the colorant to form high-resistivity phases (such as La2Ti2O7), leading to significant resistivity fluctuations and affecting the antistatic properties of the material. Moreover, this preparation method is energy-intensive (requiring two high-temperature treatments), increasing production costs. Furthermore, the tape casting process and sintering cannot simultaneously achieve both high porosity (>30%) and high strength (>60MPa) in ceramics. Summary of the Invention

[0005] To address the aforementioned problems, this invention designs a colorant with a special ratio and composition, which promotes the in-situ formation of a stable spinel phase in alumina and transition metal oxide colorants at high temperatures, making the coloring of black alumina ceramics more stable. Furthermore, due to the presence of Mn... 4+ / Fe 3+ Plasma-substituted Al 3+ The charge imbalance leads to vacancies at metal sites, further resulting in a large number of oxygen vacancy defects in the in-situ generated spinel. d-orbital electrons readily undergo transitions, forming a narrow bandgap semiconductor. This provides charge carriers, improves the material's light absorption capacity, thereby enhancing its chromaticity value, and significantly reduces the volume resistivity of the alumina ceramic to achieve antistatic properties. Therefore, this invention provides a black porous alumina ceramic with antistatic properties, high porosity, excellent black chromaticity, and good mechanical properties.

[0006] In a first aspect, the present invention provides an antistatic black porous alumina ceramic. The antistatic black porous alumina ceramic comprises a porous alumina ceramic matrix and (Fe) uniformly distributed in the alumina ceramic matrix. x Mn y Co z Ni w Al2O4 spinel, the (Fe x Mn y Co z Ni w Al2O4 spinel is produced by in-situ reaction of aluminum oxide with transition metal oxides composed of iron oxide, cobalt oxide, nickel oxide and manganese dioxide; wherein the mass ratio of iron oxide, cobalt oxide, nickel oxide and manganese dioxide is (4-10):(0.5-2):(1.5-4):(3-8).

[0007] Fe2O3 / CoO / NiO / MnO2 and Al2O3 in situ generated (Fe x Mn y Co z Ni w Al₂O₄ (x+y+z+w=1, and 0.2≤x≤0.8, 0.1≤y≤0.6, 0.05≤z≤0.2, 0.05≤w≤0.2) spinel, causes metal ions of different valence states to transition in dd orbitals. Oxygen vacancies lead to the formation of defect energy levels, further increasing the probability of electronic transitions and improving the material's ability to absorb light. In addition, the mixed valence states of some ions lead to small polaron absorption (charge transfer transition), further broadening the absorption spectrum.

[0008] Preferably, the (Fe) x Mn y Co z Ni wThe Al2O4 spinel accounts for 15%–30% of the mass of antistatic black porous alumina ceramic. If (Fe...) x Mn y Co z Ni w A low content of Al2O4 spinel is detrimental to the pure black color development of black alumina ceramics; if (Fe) content is low, it will hinder the development of a pure black color. x Mn y Co z Ni w A high content of Al2O4 spinel will lead to a decrease in the mechanical properties of black alumina ceramics, and may even prevent them from achieving an antistatic effect.

[0009] Preferably, the antistatic black porous alumina ceramic has a chromaticity value L* < 35 and a porosity of 35%–50%; more preferably, the bulk density of the antistatic black porous alumina ceramic material is 2.0–2.6 g / cm³. 3 The volume resistivity is 1×10⁻¹⁰ 9 ~1 x 10 12 Ω·cm, compressive strength is 65~150MPa.

[0010] Secondly, the present invention provides a method for preparing the aforementioned antistatic black porous alumina ceramic. The preparation method includes: (1) Alumina, colorant, sintering aid, pore-forming agent and binder are mixed to obtain a mixture; the colorant is a mixture of iron oxide, cobalt oxide, nickel oxide and manganese dioxide; the mass ratio of alumina, colorant and sintering aid is (74-86):(12-24):2; (2) The obtained mixture is ball-milled with a solvent, dried and sieved to obtain ceramic powder; (3) The ceramic powder is dry-pressed and then subjected to cold isostatic pressing to obtain a preform; (4) The preform is pre-fired and then sintered to obtain an antistatic black porous alumina ceramic.

[0011] Preferably, in step (1), the sintering aid is a mixture of silicon dioxide, calcium carbonate and magnesium oxide; preferably, the mass ratio of silicon dioxide, calcium carbonate and magnesium oxide is (0.5-1.5):(0.1-3):(0.1-6).

[0012] Preferably, in step (1), the pore-forming agent is one or more of polymethyl methacrylate, carbon, starch, flour, and sucrose; preferably, the amount of the pore-forming agent added is 30% to 40% of the total mass of alumina, colorant, and sintering aid; more preferably, the particle size of the pore-forming agent is 10 to 20 μm.

[0013] Preferably, in step (1), the binder is an aqueous solution of polyvinyl alcohol; more preferably, the mass concentration of the aqueous solution of polyvinyl alcohol is 8% to 12%; more preferably, the amount of binder added is 5% to 20% of the total mass of alumina, colorant and sintering aid.

[0014] Preferably, in step (3), the pressure of the dry pressing is 2-20 MPa and the holding time is 20-30 seconds; the pressure of the cold isostatic pressing is 150-300 MPa and the time is 5-30 min.

[0015] Preferably, in step (4), the pre-firing temperature is 500-800℃ and the time is 1-3h; the sintering is atmospheric pressure sintering; preferably, the atmospheric pressure sintering temperature is 1250-1500℃ and the time is 2-5h.

[0016] Thirdly, the present invention provides the application of the aforementioned antistatic black porous alumina ceramic in semiconductor devices.

[0017] Beneficial effects

[0018] (1) Stable and pure black color: By reacting alumina and a transition metal oxide colorant of a specific composition in situ at high temperature to form a stable spinel phase with a large number of oxygen vacancy defects, the transformation of ions is promoted, making the coloring of ceramics more stable.

[0019] (2) Synergistic regulation of color, porosity, and strength: By optimizing the ratio of ceramic materials to transition metal oxides, the compressive strength is maintained at ≥65MPa even when the porosity is ≥35%, and due to the metal ions (Fe... 3+ Co 2+ Ni 2+ Mn 4+ The d-orbital electrons of the ceramic readily undergo transitions, forming a narrow bandgap semiconductor that provides charge carriers, thereby significantly reducing the volume resistivity of the ceramic to achieve antistatic properties.

[0020] (3) By introducing colorant and pore-forming agent simultaneously through a one-time synthesis method, high porosity and black coloring effects are achieved simultaneously in a single sintering process, simplifying the preparation process.

[0021] (4) Compared with the traditional two-step sintering method, the production cycle of this invention is shorter, and the pore-forming agent is readily available, cheaper and easier to produce in China, making it possible to prepare high-performance ceramics at low cost. Attached Figure Description

[0022] Figure 1 This is a cross-sectional SEM image of an antistatic black porous alumina ceramic.

[0023] Figure 2This is the XRD pattern of an antistatic black porous alumina ceramic. Detailed Implementation

[0024] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.

[0025] The antistatic black porous alumina ceramic of the present invention comprises a porous alumina ceramic matrix and (Fe) uniformly distributed in the alumina ceramic matrix. x Mn y Co z Ni w Al2O4 spinel phase, wherein (Fe x Mn y Co z Ni w The Al₂O₄ spinel phase is formed by the in-situ reaction of aluminum oxide with transition metal oxides composed of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide. x, y, z, and w all refer to molar ratios. Since +4 valence manganese ions and oxygen ions combine to form lower valence +3 manganese ions and oxygen vacancies, a larger y value indicates a higher oxygen vacancy concentration.

[0026] The (Fe) x Mn y Co z Ni w Al₂O₄ spinel is a multi-element solid solution. In some embodiments, the (Fe) x Mn y Co z Ni w The phase composition of Al2O4 spinel includes a main crystalline phase and secondary crystalline phases; the main crystalline phases include FeAl2O4 and MnAl2O4, with contents of 30–70 mol% and 10–40 mol%, respectively; the secondary crystalline phases include CoAl2O4, NiAl2O4, and other non-stoichiometric spinel phases (e.g., Co...). 0.1 Mn 0.9 One or more of Al2O4, whose total content is 5-30 mol%.

[0027] The mass ratio of iron oxide, cobalt oxide, nickel oxide and manganese dioxide is (4-10):(0.5-2):(1.5-4):(3-8).

[0028] At high temperatures, transition metal oxides (Fe2O3 / CoO / NiO / MnO2) form a stable black spinel phase with alumina. This not only enhances the black color of the alumina ceramic but also improves carrier mobility through metal ion reduction and charge transfer, thereby reducing the volume resistivity of the ceramic and maintaining it at 1×10⁻⁶. 9~1 x 10 12 Ω·cm.

[0029] The mass ratio of the alumina to the transition metal oxide composed of iron oxide, cobalt oxide, nickel oxide and manganese dioxide can be (74-86):(12-24).

[0030] The (Fe) x Mn y Co z Ni w The Al2O4 spinel phase can account for 15% to 30% of the mass of antistatic black porous alumina ceramics.

[0031] The porous structure of the antistatic black porous alumina ceramic is a through-hole structure. For example, the pore size of the porous structure is approximately 10–20 μm.

[0032] Therefore, this invention achieves the following effects by controlling the composition and structure of antistatic black porous alumina ceramic: 1. The Fe / Ni-Co / Mn colorant combination generates a (Fe,Mn,Co,Ni)Al2O4 defect spinel phase in situ during sintering, achieving a low-cost, deep black, and highly stable coloring effect; 2. Defect design: The conductivity of the material is controlled by oxygen vacancies and mixed valence states to achieve antistatic properties; 3. Structure-function synergy: The pore-forming agent (the formed porous structure) and the spinel conductive network are integrated to achieve synergistic control of porous properties and antistatic characteristics.

[0033] The following exemplarily illustrates the preparation method of the antistatic black porous alumina ceramic of the present invention.

[0034] Alumina, colorant, sintering aid, pore-forming agent, and binder are mixed to obtain a mixture. The mixing method can be dry mixing, where the above raw materials are directly mixed. Alternatively, the mixing method can be wet mixing, where a solvent (e.g., ethanol) is added to the above raw materials for mixing.

[0035] The colorant is a mixture of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide. The mass ratio of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide is (4–10):(0.5–2):(1.5–4):(3–8). For example, the mass ratio of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide is (4.5–5.5):(0.8–1.2):(1.8–2.2):(3.8–4.2). For example, when Fe₂O₃:MnO₂≈5:4, Mn 4+ Reduce to Mn 2+ / Mn 3+ Mixed valence states, while Fe 3+ Also partially restored to These mixed valence states promote electron hopping conductivity, while the addition of CoO / NiO (Co:Ni≈1:2) forms a stable (Co,Ni)Al2O4 spinel phase, reducing Mn / Fe volatilization at high temperatures. The multi-element dd transitions of metal ions result in an L* value of ≤25 for the ceramic material, and the formation of the conductive network stabilizes the resistivity at 1×10⁻⁶. 9 ~1 x 10 12 Ω·cm.

[0036] Ti 4+ / V 5+ The valence state is relatively stable, and oxygen vacancies cannot be provided, meaning that TiO2 / V2O5 cannot form an effective defect spinel phase, resulting in poor coloring of the material. Furthermore, V2O5 is a toxic substance. 5+ Sintering at temperatures above 1200℃ can cause volatilization and environmental pollution.

[0037] The sintering aid is a mixture of silicon dioxide, calcium carbonate, and magnesium oxide. The mass ratio of silicon dioxide, calcium carbonate, and magnesium oxide is (0.5–1.5):(0.1–3):(0.1–6). For example, the mass ratio of silicon dioxide, calcium carbonate, and magnesium oxide is (0.8–1.2):(1.5–2.5):(4.5–5.5). SiO2 and CaCO3 form a sufficient amount of liquid phase at high temperatures, lowering the sintering temperature; however, excessive content can lead to an increase in the glassy phase, affecting ceramic properties. Meanwhile, MgO contains Mg... 2+ Segregation at Al2O3 grain boundaries inhibits abnormal grain growth and increases the mechanical properties of ceramics. However, the content should not be excessive, as too much will lead to the formation of magnesium aluminum spinel between MgO and Al2O3. This spinel has a wider band gap than FeAl2O4 and MnAl2O4 spinel phases, reducing electron transitions and affecting the final coloring of the ceramic. The addition of sintering aids can lower the sintering activation energy and reduce the sintering temperature of the ceramic, achieving densification at sintering temperatures of 1250℃ and above (e.g., 1250–1500℃). Black porous alumina ceramics can still maintain good compressive strength (e.g., compressive strength ≥ 65 MPa).

[0038] In some embodiments, the mass ratio of the alumina, colorant, and sintering aid may be (74-86):(12-24):2.

[0039] Commonly used pore-forming agents in this field can be used. For example, the pore-forming agent is one or a mixture of polymethyl methacrylate (PMMA), carbon, starch, flour, and sucrose. The particle size of the pore-forming agent can be 10–20 μm. The amount of the pore-forming agent added is 30%–40% of the total mass of alumina, colorant, and sintering aid. During sintering, the pore-forming agent decomposes at temperatures above 700–800°C to generate interconnected channels, thus allowing for adjustable porosity of the alumina ceramic.

[0040] A commonly used binder in the art can be used. For example, the binder is an aqueous solution of polyvinyl alcohol (PVA). Preferably, the mass concentration of the PVA aqueous solution is 8% to 12%. The amount of binder added is 5% to 20% of the total mass of alumina, colorant, and sintering aid. For example, the amount of binder added can be 10% of the total mass of alumina, colorant, and sintering aid.

[0041] The resulting mixed powder was ball-milled, dried, and sieved with a solvent to obtain ceramic powder.

[0042] The solvent includes, but is not limited to, ethanol. For example, the mass ratio of ethanol to the mixed powder is 1:1. The ball milling parameters can be adjusted as needed. For example, the ball-to-powder ratio is 3:1, the rotation speed is 160–250 rpm, and the milling time is 20–28 hours. Control of the drying temperature and drying time is a conventional technique in the art. For example, the drying temperature is 60–120°C, and the drying time is 24 hours. The sieve used for sieving can be 80–100 mesh.

[0043] The ceramic powder is dry-pressed and then subjected to cold isostatic pressing to obtain a preform. The dry-pressing pressure is 2–20 MPa, and the holding time is 20–30 seconds. The cold isostatic pressing pressure is 150–300 MPa, and the time is 5–30 minutes.

[0044] The preform is pre-fired and then sintered to obtain antistatic black porous alumina ceramic.

[0045] The pre-firing temperature is 500–800°C, and the pre-firing time is 1–3 hours (e.g., 2 hours). In some embodiments, the pre-firing heating rate is 0.5–2°C / min.

[0046] The sintering can be atmospheric pressure sintering. For example, the atmospheric pressure sintering temperature is 1250–1500°C; the atmospheric pressure sintering time is 2–5 hours. In some embodiments, the heating rate of atmospheric pressure sintering is 5–10°C / min.

[0047] As an example, the preparation method of the antistatic porous alumina ceramic includes:

[0048] Ingredients. Weigh alumina, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide, and silicon dioxide according to the mass ratio of (74-86):(5-10):(1-2):(2-4):(4-8):0.25:0.5:1.25. Weigh out the pore-forming agent and PVA aqueous solution, mix them, and then add ethanol to mix thoroughly to obtain the mixture.

[0049] Ball milling. The obtained mixture, ethanol, and high-purity alumina (grinding) balls were mixed at a mass ratio of 1:1:3 and ball milled at 160-250 rpm for 20-28 hours to obtain a uniformly mixed ball milling material.

[0050] Drying and sieving. The obtained ball mill material is dried at 60-100℃ for 24 hours and then sieved through an 80-100 mesh sieve.

[0051] Dry pressing. The sieved powder is pressed into a ceramic green body under a pressure of 2-20 MPa for 20-30 seconds.

[0052] Cold isostatic pressing. The obtained ceramic green body is subjected to cold isostatic pressing at a pressure of 150–300 MPa for 5–30 min.

[0053] Pre-firing. The cold isostatically pressed ceramic blank is placed in a muffle furnace to remove the binder, and the heating rate is 0.5-2℃ / min. It is then treated at a sintering temperature of 500-800℃ for 2 hours.

[0054] Atmospheric pressure sintering. The debinding ceramic blank is placed in a high-temperature muffle furnace for atmospheric pressure sintering at a heating rate of 5-10℃ / min and treated at a sintering temperature of 1250-1500℃ for 2-5 hours. Antistatic black porous alumina ceramic is obtained.

[0055] Testing revealed that the colorimetric value L* of the antistatic black porous alumina ceramic of this invention is <35; the porosity of the antistatic black porous alumina ceramic is 35%–50%; and the bulk density of the antistatic black porous alumina ceramic is 2.0–2.6 g / cm³. 3 The volume resistivity of the antistatic black porous alumina ceramic is 1×10⁻⁶. 9 ~1 x 10 12 The compressive strength of the antistatic black porous alumina ceramic is 65-150 MPa.

[0056] This invention also provides applications for antistatic black porous alumina ceramics. In particular, the antistatic black alumina ceramics are mainly used in semiconductor devices, such as vacuum chucks and electrostatic chucks.

[0057] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0058] Example 1

[0059] Step (1) Ingredient preparation. Weigh out aluminum oxide, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide and silicon dioxide in the mass ratio of 86g:5g:1g:2g:4g:0.25g:0.5g:1.25g. Weigh out 40g PMMA and 10g PVA solution. Mix the above raw materials and add 150g ethanol for thorough mixing to obtain the mixture.

[0060] Step (2) Mixing. The mixture obtained in step (1), ethanol and high-purity alumina balls are mixed at a mass ratio of 1:1:3 and ball-milled at 180 rpm for 24 hours to obtain a uniformly mixed ball milling material.

[0061] Step (3) Drying and sieving. The ball mill material obtained in step (2) is dried at 60°C for 24 hours and then sieved through an 80-mesh sieve.

[0062] Step (4) Dry pressing. The powder obtained in step (3) is pressed into a ceramic green body by holding it under a pressure of 15 MPa for 30 seconds.

[0063] Step (5) Cold isostatic pressing. The ceramic green body obtained in step (4) is subjected to cold isostatic pressing at a pressure of 200 MPa for 10 min.

[0064] Step (6) Pre-firing. The ceramic blank after cooling in step (5) is placed in a muffle furnace to remove the binder. The heating rate is 1℃ / min, and it is treated at 750℃ for 2 hours.

[0065] Step (7) Atmospheric pressure sintering. The ceramic blank after debinding in step (6) is placed in a high-temperature muffle furnace for atmospheric pressure sintering. The heating rate is controlled at 5℃ / min, the sintering temperature is 1450℃, and the holding time is 3h to obtain the antistatic black porous alumina ceramic.

[0066] Example 2

[0067] Step (1) Ingredient preparation. Weigh out aluminum oxide, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide, and silicon dioxide in the following mass ratios: 80g: 7g: 1.5g: 3g: 6.5g: 0.25g: 0.5g: 1.25g. Weigh out 40g of PMMA and 10g of PVA solution. Mix the above ingredients and add 150g of ethanol for thorough mixing to obtain the mixture.

[0068] Step (2) Mixing. The mixture obtained in step (1), ethanol and high-purity alumina balls are mixed at a mass ratio of 1:1:3 and ball-milled at 180 rpm for 24 hours to obtain a uniformly mixed ball milling material.

[0069] Step (3) Drying and sieving. The ball mill material obtained in step (2) is dried at 60°C for 24 hours and then sieved through a 100-mesh sieve.

[0070] Step (4) Dry pressing. The powder obtained in step (3) is pressed into a ceramic green body by holding it under a pressure of 20 MPa for 20 s.

[0071] Step (5) Cold isostatic pressing. The ceramic green body obtained in step (4) is subjected to cold isostatic pressing at a pressure of 200 MPa for 10 min.

[0072] Step (6) Pre-firing. The ceramic blank after cooling in step (5) is placed in a muffle furnace to remove the binder. The heating rate is 1℃ / min, and it is treated at 700℃ for 2 hours.

[0073] Step (7) Atmospheric pressure sintering. The ceramic blank after debinding in step (6) is placed in a high-temperature muffle furnace for atmospheric pressure sintering. The heating rate is controlled at 5℃ / min, the sintering temperature is 1500℃, and the holding time is 3h to obtain the antistatic black porous alumina ceramic.

[0074] Example 3

[0075] Step (1) Ingredient preparation. Weigh out aluminum oxide, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide and silicon dioxide in the mass ratio of 74g:10g:2g:4g:8g:0.25g:0.5g:1.25g. Weigh out 50g PMMA and 12g PVA aqueous solution. Mix the above raw materials and add 162g ethanol for thorough mixing to obtain the mixture.

[0076] Step (2) Mixing. The mixture obtained in step (1), ethanol and high-purity alumina balls are mixed at a mass ratio of 1:1:3 and ball-milled at 180 rpm for 24 hours to obtain a uniformly mixed ball milling material.

[0077] Step (3) Drying and sieving. The ball mill material obtained in step (2) is dried at 60°C for 24 hours and then sieved through a 100-mesh sieve.

[0078] Step (4) Dry pressing. The powder obtained in step (3) is pressed into a ceramic green body by holding it under a pressure of 30 MPa for 20 seconds.

[0079] Step (5) Cold isostatic pressing. The ceramic green body obtained in step (4) is subjected to cold isostatic pressing at a pressure of 200 MPa for 10 min.

[0080] Step (6) Pre-firing. The ceramic blank after cooling in step (5) is placed in a muffle furnace to remove the binder. The heating rate is 1℃ / min, and it is treated at 800℃ for 2 hours.

[0081] Step (7) Atmospheric pressure sintering. The ceramic blank after debinding in step (6) is placed in a high-temperature muffle furnace for atmospheric pressure sintering. The heating rate is controlled at 5℃ / min, the sintering temperature is 1400℃, and the holding time is 3h to obtain the antistatic black porous alumina ceramic.

[0082] Example 4

[0083] The only difference between this embodiment and Embodiment 1 is that the sintering temperature at atmospheric pressure is 1350℃, while the other raw material conditions and process parameters are exactly the same as in Embodiment 1.

[0084] Example 5

[0085] The only difference between this embodiment and Embodiment 2 is that the sintering temperature at atmospheric pressure is 1400℃, while the other raw material conditions and process parameters are exactly the same as in Embodiment 2.

[0086] Example 6

[0087] The only difference between this embodiment and Embodiment 1 is that the holding time for atmospheric pressure sintering is 4 hours, while the other raw material conditions and process parameters are exactly the same as in Embodiment 1.

[0088] Example 7

[0089] The only difference between this embodiment and Embodiment 2 is that the holding time for atmospheric pressure sintering is 5 hours, while the other raw material conditions and process parameters are exactly the same as in Embodiment 2.

[0090] Comparative Example 1

[0091] The only difference between this comparative example and Example 1 is that no pore-forming agent is added to the raw materials; all other raw material conditions and process parameters are exactly the same as in Example 1.

[0092] Comparative Example 2

[0093] The only difference between this comparative example and Example 1 is that aluminum oxide, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide, and silicon dioxide were weighed in a mass ratio of 88g:8g:0.5g:0.5g:1g:0.25g:0.5g:1.25g, i.e., the ratio of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide in the raw materials is 8:0.5:0.5:1 (mass ratio). All other raw material conditions and process parameters are exactly the same as in Example 1.

[0094] Comparative Example 3

[0095] The only difference between this comparative example and Example 1 is that iron oxide in the raw materials is replaced with chromium oxide, while the other raw material ratios, conditions and process parameters are exactly the same as in Example 1.

[0096] Comparative Example 4

[0097] The only difference between this comparative example and Example 1 is that nickel oxide is omitted, and aluminum oxide, iron oxide, cobalt oxide, manganese dioxide, calcium carbonate, magnesium oxide, and silicon dioxide are weighed according to a mass ratio of 88g:5g:1g:4g:0.25g:0.5g:1.25g. That is, the ratio of iron oxide, cobalt oxide, and manganese dioxide in the raw materials is 5:1:4 (mass ratio). The other raw material ratios, conditions, and process parameters are exactly the same as in Example 1.

[0098] Comparative Example 5

[0099] The only difference between this comparative example and Example 1 is that alumina, iron oxide, cobalt oxide, nickel oxide, manganese dioxide, calcium carbonate, magnesium oxide, and silicon dioxide were weighed in a mass ratio of 93g:2g:0.5g:0.5g:2g:0.25g:0.5g:1.25g, i.e., the ratio of iron oxide, cobalt oxide, nickel oxide, and manganese dioxide in the raw materials is 2:0.5:0.5:2 (mass ratio). The amount of colorant added is significantly lower than that of this invention. The other raw material ratios, conditions, and process parameters are exactly the same as those in Example 1.

[0100] Figure 1 The image shows a cross-sectional SEM image of the antistatic black porous alumina ceramic prepared in Example 1. It can be seen that the dark areas are black mixed spinel phases, and the light areas are alumina phases. The pore size is approximately 20 μm, indicating a through-pore structure.

[0101] Figure 2 The XRD diffraction pattern of the antistatic, black porous alumina ceramic prepared in Example 1 is shown. It can be seen that it consists of an alumina phase and a mixed spinel phase, corresponding to Al2O3 (PDF#83-2080) and a mixed spinel phase (PDF#76-0072), mainly composed of FeAl2O4, MnAl2O4, and Co. 0.1 Mn 0.9 The Al₂O₄ contains three spinel phases, with a molar ratio of approximately 10:4:3. No other phases were found.

[0102] Performance testing: The colorimetric value of the ceramic was tested using a precision colorimeter; the bulk density and porosity of the ceramic were tested using Archimedes' water displacement method; the volume resistivity of the ceramic was tested using a high-resistivity meter; and the compressive strength of the ceramic was tested using a universal testing machine with a loading rate of 0.5 mm / min.

[0103] The main performance parameters of the antistatic black porous alumina ceramics prepared in each embodiment and comparative example are shown in Table 1.

[0104] Table 1

[0105] As shown in Table 1, the antistatic black porous alumina ceramic prepared by this invention has a chromaticity value L* < 35, a porosity ≥ 35%, and a compressive strength ≥ 65 MPa. While ensuring stable black color development and high porosity, it also possesses antistatic properties and good mechanical properties. In Comparative Example 1, the ceramic has very low porosity due to the absence of a pore-forming agent; in Comparative Example 2, the ceramic's color is grayish-black due to an imbalance in the proportion of transition metal oxides in the colorant, resulting in a higher chromaticity value L*; in Comparative Example 3, Cr... 3+ The dd transition (absorption at 450 / 600nm) mainly appears as a blackish-green color, and cannot achieve pure black; and Cr 3+ The relatively stable structure, lacking oxygen vacancy defects, leads to a reduction in conductive channels and inhibits electron transitions, resulting in higher resistivity. In Comparative Example 4, the absence of NiO leads to Ni... 2+ The disappearance of the 400nm absorption peak results in incomplete absorption spectrum coverage of the material, high chromaticity value, and the absence of Ni. 2+ Auxiliary charge transfer leads to Mn 3+ / Fe 2+ The incomplete conductive network results in a high overall volume resistivity. In Comparative Example 5, the amount of colorant added was reduced to 5 wt%, which prevented the continuous formation of the spinel phase, leading to unstable coloring. Furthermore, the low content of transition metal oxides resulted in insufficient oxygen vacancies and mixed valence states, causing the ceramic material to lose its antistatic properties. Additionally, the lack of spinel phase caused the sintering of the liquid phase to partially close the pores inside the material, resulting in a low porosity of the ceramic.

[0106] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. An antistatic black porous alumina ceramic, characterized in that, The antistatic black porous alumina ceramic comprises a porous alumina ceramic matrix and Fe2O3 uniformly distributed in the alumina ceramic matrix. x Mn y Co z Ni w Al₂O₄ spinel, wherein x + y + z + w = ​​1, 0.2 ≤ x ≤ 0.8, 0.1 ≤ y ≤ 0.6, 0.05 ≤ z ≤ 0.2, 0.05 ≤ w ≤ 0.2; the (Fe x Mn y Co z Ni w Al2O4 spinel is produced by in-situ reaction of aluminum oxide with transition metal oxides composed of iron oxide, cobalt oxide, nickel oxide and manganese dioxide; the mass ratio of iron oxide, cobalt oxide, nickel oxide and manganese dioxide is (4-10):(0.5-2):(1.5-4):(3-8).

2. The antistatic black porous alumina ceramic according to claim 1, characterized in that, The (Fe) x Mn y Co z Ni w Al2O4 spinel accounts for 15% to 30% of the mass of antistatic black porous alumina ceramic.

3. The antistatic black porous alumina ceramic according to claim 1 or 2, characterized in that, The antistatic black porous alumina ceramic has a chromaticity value L* < 35 and a porosity of 35%–50%; preferably, the bulk density of the antistatic black porous alumina ceramic is 2.0–2.6 g / cm³. 3 The volume resistivity is 1×10⁻¹⁰ 9 ~1 x 10 12 Ω·cm, compressive strength is 65~150MPa.

4. The method for preparing antistatic black porous alumina ceramic according to any one of claims 1 to 3, characterized in that, The preparation method includes: (1) Alumina, colorant, sintering aid, pore-forming agent and binder are mixed to obtain a mixture; the colorant is a mixture of iron oxide, cobalt oxide, nickel oxide and manganese dioxide; the mass ratio of alumina, colorant and sintering aid is (74-86):(12-24):2; (2) The obtained mixture is ball-milled with a solvent, dried and sieved to obtain ceramic powder; (3) The ceramic powder is dry-pressed and then subjected to cold isostatic pressing to obtain a preform; (4) The preform is pre-fired and then sintered to obtain an antistatic black porous alumina ceramic.

5. The preparation method according to claim 4, characterized in that, In step (1), the sintering aid is a mixture of silicon dioxide, calcium carbonate and magnesium oxide; preferably, the mass ratio of silicon dioxide, calcium carbonate and magnesium oxide is (0.5-1.5):(0.1-3):(0.1-6).

6. The preparation method according to claim 4 or 5, characterized in that, In step (1), the pore-forming agent is one or more of polymethyl methacrylate, carbon, starch, flour, and sucrose; preferably, the amount of the pore-forming agent added is 30% to 40% of the total mass of alumina, colorant, and sintering aid; more preferably, the particle size of the pore-forming agent is 10 to 20 μm.

7. The preparation method according to any one of claims 4 to 6, characterized in that, In step (1), the binder is an aqueous solution of polyvinyl alcohol; preferably, the mass concentration of the aqueous solution of polyvinyl alcohol is 8% to 12%; more preferably, the amount of binder added is 5% to 20% of the total mass of alumina, colorant and sintering aid.

8. The preparation method according to any one of claims 4 to 7, characterized in that, In step (3), the pressure of the dry pressing is 2-20 MPa and the holding time is 20-30 seconds; the pressure of the cold isostatic pressing is 150-300 MPa and the time is 5-30 min.

9. The preparation method according to any one of claims 4 to 8, characterized in that, In step (4), the pre-firing temperature is 500-800℃ and the time is 1-3h; the sintering is atmospheric pressure sintering; preferably, the atmospheric pressure sintering temperature is 1250-1500℃ and the time is 2-5h.

10. The application of an antistatic black porous alumina ceramic according to any one of claims 1 to 3 in a semiconductor device.

Citation Information

Patent Citations

  • A black alumina ceramic powder, a black alumina ceramic body made of it and a process for producing the black alumina ceramic body

    CN107406328A